Beban Kerja Perawat Berhubungan Dengan Kelengkapan Pendokumentasian Asuhan Keperawatan Rawat Inap RSUD Panembahan Senopati Bantul - Dewi Khoirunnissa; Agus Sarwo Prayogi; Tri Arini (POLTEKKES KEMENKES YOGYAKARTA, 2019)
Complete documentation of the Deputy Secretary is very important for nurses' responsibilities and responsibilities for the tasks that have been carried out. The heavy workload of nurses can affect the documentation of health insurance.To determine the relationship of nurse workload with the completeness nursing documentation in the Inpatient Room of Panembahan Senopati Hospital Bantul Yogyakarta.Type of quantitative descriptive research with cross sectional approach. The population of nurses in the inpatient room of Panembahan Senopati Hospital Bantul. The sampling technique was purposive sampling, the samples was 47 educated nurses DIII Nursing, DIV Nursing and Nurses. The research instrument used the nurse's workload questionnaire and the observation checklist of documentary documents. The nurse workload questionnaire has been tested for validity with the results of count> 0.361, and the reliability test results of alpha cronbach's value of 0.945. Data analysis techniques using Kendall-Tau. Nurses workload with high category (25.5%), moderate (59.6%), and low (14.9%). The level of complete documentation of nursing care was in the good category (36.2%), sufficient (46.8%), and less (17.0%). The results of the statistical test show the magnitude of the Kendall-Tau correlation coefficient of -0.492 with a significance of 0.000. This shows that the value of p <0.05 means that there is a negative and significant relationship between the workload of nurses and the complete documentation of nursing care. The workload of nurses influences the complete documentation of nursing care. This is because workload is influenced by the number of procedures that must be carried out by nurses to patients according to their level of dependence and can affect the quality of performance nurses.